Decentralization, Strategy, and Effectiveness of Strategic Business Units in Multibusiness Organizations - Govindarajan, Vijay (Academy of Management Review, 1986)
The relationship between decentralization and the effectiveness of strategic business units (SBUs) within multibusiness organizations is examined. Three strategic continua are considered—Gupta and Govindarajan's (1984) build-harvest, Porter's (1980) differentiation-low cost, and Miles and Snow's (1978) prospector-defender; in each case it is proposed that the degree of decentralization of decision-making authority delegated to the general manager of the SBU should be closely aligned with the SBU's strategy to optimize the effectiveness of the SBU.